Penerapan Distribution Requirement Planning (DRP) pada Central Warehouse PT. Coca Cola Amatil Bottle Pandaan - Garside, Annisa Kesy (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
This research has a good to plan the product delivery schedule from central ware house to each ware house and from ware house to PT. Coca Cola outlet to minimize the holding number of product. To plan this schedule we implement DRP (Distribution Requirement Planning) method. With using the product demand data, lead time of delivery, holding cost and release cost, also BOD (Bill of Distribution). Then analysis them using DRP software to find the shipping schedule. After implementing DRP method PT. Coca Cola can decrease about RP 7.205.761.500,00 for 8 week.